2024
DOI: 10.1021/acs.energyfuels.3c03843
|View full text |Cite
|
Sign up to set email alerts
|

Advances and Prospects of Supercritical CO2 for Shale Gas Extraction and Geological Sequestration in Gas Shale Reservoirs

Weijun Shen,
Tianran Ma,
Luo Zuo
et al.

Abstract: The advancements in hydraulic fracturing and horizontal drilling techniques have substantially facilitated the large-scale extraction of natural gas from shale gas reservoirs. However, the use of fracking water poses several potential drawbacks including the contamination of groundwater, surface water, and soil, as well as risks to air quality. Due to the unique physical properties of supercritical CO2, shale gas exploitation using this method has been considered a promising technology that can not only improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 113 publications
0
3
0
Order By: Relevance
“…Stable roadway spaces can be stored in artificially reconstructed storage tanks with a supercritical storage capacity. The burial depth of coal in China is generally 500-1000 m. The feasibility of CO 2 storage in the goaf of medium and shallow coal mining is a topic of concern for Chinese geologists [14,[20][21][22][23]33]. A pilot experiment for CO 2 storage was conducted in the Southern Shanxi Formation of the Qinshui Basin in Shanxi Province (buried at depths of 472.34~478.70 m), with an injection of 192.8 tons of liquid CO 2 .…”
Section: Co2 Physical Trappingmentioning
confidence: 99%
See 2 more Smart Citations
“…Stable roadway spaces can be stored in artificially reconstructed storage tanks with a supercritical storage capacity. The burial depth of coal in China is generally 500-1000 m. The feasibility of CO 2 storage in the goaf of medium and shallow coal mining is a topic of concern for Chinese geologists [14,[20][21][22][23]33]. A pilot experiment for CO 2 storage was conducted in the Southern Shanxi Formation of the Qinshui Basin in Shanxi Province (buried at depths of 472.34~478.70 m), with an injection of 192.8 tons of liquid CO 2 .…”
Section: Co2 Physical Trappingmentioning
confidence: 99%
“…A pilot experiment for CO 2 storage was conducted in the Southern Shanxi Formation of the Qinshui Basin in Shanxi Province (buried at depths of 472.34~478.70 m), with an injection of 192.8 tons of liquid CO 2 . The storage effect was satisfactory [14,33]. Wang et al [21] studied the occurrence conditions of natural CO 2 in the Yaojie mining area of Gansu Province (<400 m) and concluded that it is feasible to store CO 2 in coal goaf.…”
Section: Co2 Physical Trappingmentioning
confidence: 99%
See 1 more Smart Citation